Effect of current pattern and conductive phase on sintering behavior of Si3N4-based ceramic composite. Issue 8 (1st June 2018) - Zuo, Fei; Meng, Fan; Lin, Dong-Tao; Lv, Jian; Yu, Jun-Jie; Chen, Qiang; Wang, Hong-Jian; He, Fu-Po; Senger, Marco; Lin, Hua-Tay
Abstract: The objective of this investigation is to provide insights into the phenomenon and mechanism(s) involved in the current-assisted sintering of Si3 N4 -based ceramic composite. The effects of continuous electric current, pulsed electric current, and amount and particle size of TiN conductive phase on the densification behaviors, α-β phase transformation, and microstructure of sintered samples were analyzed and compared in this study. Results showed that the combined effect of the employed current pattern and conductive phase mainly worked at the stage of liquid formation and particle rearrangement during the sintering process. The solution-precipitation process related to α-β phase transformation was only influenced by the presence of the TiN conductive phase owning fine particle size. It is suggested that the particle size and distribution of the TiN conductive phase have an apparent impact on the sintering behavior and final characteristics of the non-conductive Si3 N4 matrix during the current-assisted sintering process.